2011
DOI: 10.3945/ajcn.111.015206
|View full text |Cite
|
Sign up to set email alerts
|

Hiding vegetables to reduce energy density: an effective strategy to increase children’s vegetable intake and reduce energy intake

Abstract: The incorporation of substantial amounts of puréed vegetables to reduce the ED of foods is an effective strategy to increase the daily vegetable intake and decrease the energy intake in young children. This trial was registered at clinicaltrials.gov as NCT01252433.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
0
8

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(71 citation statements)
references
References 27 publications
2
60
0
8
Order By: Relevance
“…These studies clearly demonstrate the potential to employ more novel strategies for decreasing children's EI, while at the same time not compromising on palatability. Spill et al (79) also recently demonstrated that incorporating pureed vegetables into multiple meals, to achieve a 25 % decrease in ED, resulted in a down-regulation of preschool children's EI by 12 % (3-5-year-old boys and girls, n 40). Interestingly this reduction in EI persisted over a full day, and moreover, children did not compensate by consuming greater quantities of the un-manipulated snacks and side dishes offered throughout the day, as might have been hypothesised (79) .…”
Section: Additive Effects Of Portion Size and Energy Density On Energmentioning
confidence: 98%
“…These studies clearly demonstrate the potential to employ more novel strategies for decreasing children's EI, while at the same time not compromising on palatability. Spill et al (79) also recently demonstrated that incorporating pureed vegetables into multiple meals, to achieve a 25 % decrease in ED, resulted in a down-regulation of preschool children's EI by 12 % (3-5-year-old boys and girls, n 40). Interestingly this reduction in EI persisted over a full day, and moreover, children did not compensate by consuming greater quantities of the un-manipulated snacks and side dishes offered throughout the day, as might have been hypothesised (79) .…”
Section: Additive Effects Of Portion Size and Energy Density On Energmentioning
confidence: 98%
“…Caton et al, 2013;de Wild et al, 2013) • Vegetables by stealth, such as incorporating pureed vegetable into an entrée (e.g. Spill et al, 2011a) Food services…”
mentioning
confidence: 99%
“…Le camouflage consiste à intégrer des aliments, le plus souvent des légumes, dans d'autres aliments sans que l'enfant le détecte. À court terme, cela permet d'augmenter la consommation de légumes tout en diminuant la densité calorique des mets (Leahy et al, 2008;Blatt et al, 2011;Spill et al, 2011).…”
Section: Discussionunclassified
“…Toutefois, il est important que ce ne soit pas la seule façon de présenter un aliment plus ou moins apprécié (Spill et al, 2011). En complément à cette approche, le légume moins apprécié doit aussi être présenté dans sa forme entière.…”
Section: Discussionunclassified